2017
DOI: 10.1038/ncomms13906
|View full text |Cite
|
Sign up to set email alerts
|

Slow cooling and efficient extraction of C-exciton hot carriers in MoS2 monolayer

Abstract: In emerging optoelectronic applications, such as water photolysis, exciton fission and novel photovoltaics involving low-dimensional nanomaterials, hot-carrier relaxation and extraction mechanisms play an indispensable and intriguing role in their photo-electron conversion processes. Two-dimensional transition metal dichalcogenides have attracted much attention in above fields recently; however, insight into the relaxation mechanism of hot electron-hole pairs in the band nesting region denoted as C-excitons, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
172
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(190 citation statements)
references
References 56 publications
(67 reference statements)
16
172
2
Order By: Relevance
“…Different from previously reported timescales within hundreds of femtoseconds, the decay profiles of C exciton were fitted with a biexponential attenuation function (red solid line) with two different time‐components: τ 1 (1.4 ± 0.2 ps) andτ2 (13.5 ± 1 ps). Such results also differ from recent study in which a super‐slow cooling process in C exciton is reported but the cooling process keeps in a timescale with hundreds of picoseconds . The dynamics of exciton C remains controversial to date.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Different from previously reported timescales within hundreds of femtoseconds, the decay profiles of C exciton were fitted with a biexponential attenuation function (red solid line) with two different time‐components: τ 1 (1.4 ± 0.2 ps) andτ2 (13.5 ± 1 ps). Such results also differ from recent study in which a super‐slow cooling process in C exciton is reported but the cooling process keeps in a timescale with hundreds of picoseconds . The dynamics of exciton C remains controversial to date.…”
Section: Resultscontrasting
confidence: 99%
“…The difference in increased amplitude of the two time constants may be ascribed to the difference between different species of phonon modes in monolayer MoS 2 . Compared to the previous study reported by Wang et al, our results demonstrate a relatively fast C exciton cooling within tens of picoseconds than them with hundreds of picoseconds. The reason can be attributed to abundant defect states in CVD‐synthesized ML MoS 2 films, involving sulfur and molybdenum vacancies and interstitials, grain boundaries, and dislocations, could rapidly capture band‐edge excitons in sub‐picosecond timescale via nonradiative recombination channels (see Figure S2, Supporting Information).…”
Section: Resultscontrasting
confidence: 79%
See 2 more Smart Citations
“…The transient absorption spectrum of MoS2 on quartz substrate with an optical excitation of 2.33 eV consists of A, B and C excitonic bands centered at 1.85 eV, 1.99 eV and 2.91 eV, respectively, saturated at a delay time of about 750 fs. The formation of C exciton band with 2.33 eV excitation is attributed to upconversion [40]. The transient absorption spectrum of MoS2 is strongly modified due to GaN substrate.…”
Section: Mos2mentioning
confidence: 99%